Mini-open Repair of the Floating Anterior Inferior Glenohumeral Ligament: Combined Treatment of Bankart and Humeral Avulsion of the Glenohumeral Ligament Lesions - Zachary S. Aman, B.A.; Mitchell I. Kennedy, B.S.; Anthony Sanchez, B.S.; Joseph J. Krob, B.A.; Colin P. Murphy, B.A.; Connor G. Ziegler, M.D.; Matthew T. Provencher, M.D., MC, USNR (Arthroscopy Techniques, 2018)
Anterior shoulder instability often results from avulsion of the anterior inferior glenohumeral ligament (aIGHL) off its insertion on the glenoid, yielding a Bankart lesion. Although less common, avulsion of the ligament attachment to the humerus results in a humeral avulsion of the glenohumeral ligament (HAGL) lesion. Combined Bankart and HAGL lesions, also termed the “floating aIGHL,” create a complex pathology that is not detailed significantly in the literature. We believe a mini-open approach is a viable and reproducible procedure for treatment because it allows for protection of the axillary nerve and other neurovascular structures while providing optimal exposure to both the humeral insertion site of the distal aIGHL and the Bankart lesion, ensuring anatomic restoration. The purpose of this Technical Note is to describe our preferred technique to surgically treat the floating aIGHL, consisting of an anterior HAGL and concomitant Bankart lesion repair through a mini-open approach.